2022
DOI: 10.3389/fmicb.2022.871148
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Patterns of Swainsonine Presence in Morning Glories

Abstract: Endosymbionts play important roles in the life cycles of many macro-organisms. The indolizidine alkaloid swainsonine is produced by heritable fungi that occurs in diverse plant families, such as locoweeds (Fabaceae) and morning glories (Convolvulaceae) plus two species of Malvaceae. Swainsonine is known for its toxic effects on livestock following the ingestion of locoweeds and the potential for pharmaceutical applications. We sampled and tested herbarium seed samples (n = 983) from 244 morning glory species f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…In grasses, Epichlo€ e infection has been found to reduce seed predation of symbiotic grasses by rodents (Uchitel et al, 2011) and birds (Madej & Clay, 1991). Herein, using data from Cook et al (2019), Beaulieu et al (2021), Quach et al (2022), and new IDT data, we find that species with secondary metabolites produced by an endosymbiont (EA, IDT, or SWN) have significantly larger seed size than those lacking the symbiosis (55.7 mg vs 32.7 mg, P = 0.0005, respectively). Interestingly, we found that within EA+ species, those that are also IDT+ have smaller, but nonsignificant, seed size than IDTÀ species (47.0 and 60.8 mg, respectively), suggesting that the production of additional types of alkaloids may involve additional costs to the host plant or is dependent on the endosymbiont species.…”
Section: Life-history Traits Correlation With Heritable Fungal Endosy...mentioning
confidence: 78%
See 2 more Smart Citations
“…In grasses, Epichlo€ e infection has been found to reduce seed predation of symbiotic grasses by rodents (Uchitel et al, 2011) and birds (Madej & Clay, 1991). Herein, using data from Cook et al (2019), Beaulieu et al (2021), Quach et al (2022), and new IDT data, we find that species with secondary metabolites produced by an endosymbiont (EA, IDT, or SWN) have significantly larger seed size than those lacking the symbiosis (55.7 mg vs 32.7 mg, P = 0.0005, respectively). Interestingly, we found that within EA+ species, those that are also IDT+ have smaller, but nonsignificant, seed size than IDTÀ species (47.0 and 60.8 mg, respectively), suggesting that the production of additional types of alkaloids may involve additional costs to the host plant or is dependent on the endosymbiont species.…”
Section: Life-history Traits Correlation With Heritable Fungal Endosy...mentioning
confidence: 78%
“…Notably, the SWN‐producing endosymbionts in morning glories are unrelated to those in locoweed legumes and to the Periglandula endosymbionts in other morning glories (Fig. 2; Quach et al ., 2022). Outside of these three families (Convolvulaceae, Fabaceae, and Poaceae), there is little evidence of widespread heritable fungal endosymbiosis in plants.…”
Section: Hereditary Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…As alkaloid-synthesizing herbaceous legumes, locoweeds including toxic Oxytropis and Astraglus species are collectively responsible for the majority of livestock poisoning losses and seriously threaten animal husbandry on grasslands in China and the United States . Locoweeds have an impact not only on the livestock industry but also on ecology because locoweeds such as Oxytropis ochrocephala have evolved in a variety of adaptations, including drought, cold, and salt tolerance; as a result, they have replaced other plants and become dominant in the rangeland plant communities. , Swainsonine is the main toxic component of locoweed plants, and its chemical structure is shown in Figure S1, which can bring about livestock poisoning such as locoism marked by nervous system disorder. , In addition, the depression, behavior alteration, loss of weight, and even death of livestock may be caused by the ingestion of swainsonine-containing plants, and economic losses have been estimated to be tens of millions of dollars annually …”
Section: Introductionmentioning
confidence: 99%
“…4,5 In addition, the depression, behavior alteration, loss of weight, and even death of livestock may be caused by the ingestion of swainsonine-containing plants, and economic losses have been estimated to be tens of millions of dollars annually. 6 Liver inflammation is responsible for 32,000 deaths in the United States 7 and more than 1 million deaths every year worldwide. 8 Emerging evidence linking to liver diseases is related to intestinal disorders and hepatic metabolism, mainly via the gut−liver axis.…”
Section: ■ Introductionmentioning
confidence: 99%